2021
DOI: 10.3389/fnhum.2021.732974
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive-Vestibular Compensation Hypothesis: How Cognitive Impairments Might Be the Cost of Coping With Compensation

Abstract: Previous research in vestibular cognition has clearly demonstrated a link between the vestibular system and several cognitive and emotional functions. However, the most coherent results supporting this link come from rodent models and healthy human participants artificial stimulation models. Human research with vestibular-damaged patients shows much more variability in the observed results, mostly because of the heterogeneity of vestibular loss (VL), and the interindividual differences in the natural vestibula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Since oxytocin facilitates prosocial behavior in rodents [ 46 ] it would be interesting to compare the vestibular compensation with animals housed in groups. More broadly, given the beneficial role of oxytocin in the modulation of stress and anxiety [ 47 , 48 ], it would be interesting to test the effect of this neurohormone on the affective-emotional component present in vestibular pathology [ 49 , 50 ], including persistent postural-perceptual dizziness [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since oxytocin facilitates prosocial behavior in rodents [ 46 ] it would be interesting to compare the vestibular compensation with animals housed in groups. More broadly, given the beneficial role of oxytocin in the modulation of stress and anxiety [ 47 , 48 ], it would be interesting to test the effect of this neurohormone on the affective-emotional component present in vestibular pathology [ 49 , 50 ], including persistent postural-perceptual dizziness [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lacroix et al (12) have suggested that Kahneman's Capacity Model of Attention might be usefully applied to the understanding of cognitive deficits associated with vestibular loss, and especially the variability in these amongst patients. The concept is that there is a limited quantity of cognitive resources that can be allocated to cognitive tasks during recovery from vestibular loss.…”
Section: Schöberl Et Al (mentioning
confidence: 99%
“…More evidence for this has been published in both humans and animals; however, the human studies present a more complex and varied picture, with some studies showing less severe effects or more circumscribed effects [e.g., novel spatial information but not familiar spatial information (5)]. Inevitably, because the studies in patients involve an heterogeneous array of vestibular disorders, with different degrees of vestibular dysfunction, sometimes confounded by concurrent hearing loss, and different time courses, the effects of vestibular loss on cognition are bound to be more variable, and may be explained partly by Lacroix et al's (12) reference to Kahneman's Capacity Model of Attention. The evidence that vestibular loss increases the risk of AD is also gradually accumulating (2).…”
Section: Animal Studiesmentioning
confidence: 99%
“…11,[17][18][19] In addition to secondary difficulties with compensating and adjusting to living with a vestibular disorder. 20 Importantly, psychological factors can instigate and aggravate dizziness and prolong the impact of vestibular disorders, with complex vicious circles of interaction at play. 21 Anxiety and depression have been linked to poorer clinical recovery, increased perception of symptom severity, and a higher likelihood of vestibular disorder recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations to vestibulocortical networks involving brain regions implicated in memory, attention, and emotion regulation are thought to underlie this association 11,17–19 . In addition to secondary difficulties with compensating and adjusting to living with a vestibular disorder 20 …”
Section: Introductionmentioning
confidence: 99%